2004
DOI: 10.1128/mcb.24.19.8418-8427.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular FLIP Inhibits β-Catenin Ubiquitylation and Enhances Wnt Signaling

Abstract: Ligation of death receptors, such as Fas, triggers apoptosis in many types of cells (28), which is inhibited by cellular FLIP (cFLIP, also known as I-FLICE, FLAME-I, Casper, CASH, MRIT and Usurpin) (8,11,13,16,34,40,41,44). The long form of cFLIP (cFLIP-L) is highly homologous to caspase 8, containing two death effector domains (DED) and a caspaselike domain at the amino and carboxy termini, respectively. cFLIP-L, however, does not have caspase activity due to the lack of a conserved cysteine residue in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 50 publications
(77 reference statements)
4
43
0
Order By: Relevance
“…We were not able to detect p22 of cFLIP L and cFLIP S in the TRAIL or CD95L DISC of cFLIP L -or cFLIP S -expressing melanoma cells, suggesting cell-type specific differences when compared to the published data (Golks et al, 2006). In addition, it is tempting to speculate that such cFLIP fragments or uncleaved cFLIP L itself may modulate important apoptosis-independent signaling pathways such as Wnt (Naito et al, 2004) cytotoxic agents (Ivanov and Hei, 2006) or imatinib (Hamai et al, 2006) sensitized resistant melanomas to TRAIL-mediated apoptosis. However, transient transfection studies might be hampered by the activation of cellular responses due to toxic effects of the transfection procedure.…”
mentioning
confidence: 69%
“…We were not able to detect p22 of cFLIP L and cFLIP S in the TRAIL or CD95L DISC of cFLIP L -or cFLIP S -expressing melanoma cells, suggesting cell-type specific differences when compared to the published data (Golks et al, 2006). In addition, it is tempting to speculate that such cFLIP fragments or uncleaved cFLIP L itself may modulate important apoptosis-independent signaling pathways such as Wnt (Naito et al, 2004) cytotoxic agents (Ivanov and Hei, 2006) or imatinib (Hamai et al, 2006) sensitized resistant melanomas to TRAIL-mediated apoptosis. However, transient transfection studies might be hampered by the activation of cellular responses due to toxic effects of the transfection procedure.…”
mentioning
confidence: 69%
“…We, and others, previously reported that cFLIP-L enhances Wnt signaling by inhibiting ubiquitylation of -catenin, which is a mediator of canonical Wnt signaling (Naito et al, 2004;Nakagiri et al, 2005). In unstimulated cells, free cytosolic -catenin is maintained at a low level by serine or threonine phosphorylation of -catenin, followed by ubiquitylation and degradation by the proteasome.…”
Section: Introductionmentioning
confidence: 84%
“…At another level, undoubtedly more proteins will be added to the mix that comprise DED-mediated signaling platforms (such as TRAF1, TRAF2 and Raf1 as mentioned above and others), and elucidating if and how these proteins integrate with any of the core DED family members to activate various signaling pathways will represent another initial yet crucial step in answering the posed questions. Along with these challenges, new and exciting frontiers involving DED family members are being discovered and a few examples include: induction of programmed cell death from locations outside of death receptors including unligated integrins (Stupack et al, 2001(Stupack et al, , 2006 and the mitochondria (Lee et al, 2007), regulation of autophagy (and autophagic cell death) by caspase-8 and FADD (Yu et al, 2004;Pyo et al, 2005;Thorburn et al, 2005), regulation of JNK (Nakajima et al, 2006) and WNT signaling by c-FLIP L (Naito et al, 2004;Nakagiri et al, 2005), and modulation of gene expression from the androgen receptor (Qi et al, 2007) and p53 by procaspase-8 (Yao et al, 2007). The increasingly complex involvement of DED proteins in different pathways and cellular processes is indeed unfolding from ongoing effort, and additional answers that verify and map out these new connections lie ahead.…”
Section: Discussionmentioning
confidence: 99%